The Influence of Non-Linguistic Factors on Arabic Writing Motivation among Students at UIN Sunan Kalijaga - Alief, Muhammad (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Low motivation in Arabic writing remains a persistent challenge in Arabic language learning, highlighting the need to explore influential non-linguistic factors. This study aims to examine the influence of self-efficacy, learning environment, and social support on students’ motivation for Arabic writing (dāfi‘iyyah al-kitābah) in the Arabic Language Education Program at UIN Sunan Kalijaga. Employing a quantitative correlational design, data were collected from 30 students through a Likert-scale questionnaire with established validity and high reliability (α = 0.87). The results reveal that all three variables significantly influence writing motivation (p < 0.05), with self-efficacy emerging as the strongest predictor. The regression model explains 63% of the variance (R² = 0.63), indicating the substantial role of psychological and contextual factors. These findings contribute to motivation theory by reinforcing the importance of internal beliefs and external support systems in language learning. Practically, the study suggests that enhancing students’ confidence, creating a supportive learning environment, and strengthening social support can effectively improve Arabic writing motivation.